2007
DOI: 10.1088/1009-0630/9/4/25
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations on Trigger Characteristics of Pseudo-spark Switch Based on Surface Flashover Technology

Abstract: A trigger device and a triggered pseudospark switch (TPSS) were designed based on surface flashover technology, in order to meet the requirements from present pulse power technology and pulse current test technology such as a long lifetime, reliability in a wide voltage range, a short delay time, as well as small delay jitters. The trigger devices were made from different dielectric materials, with their permittivities from tens to thousands. The trigger characteristics of TPSS were investigated. The results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…From the theory of surface flashover trigger, it is shown that the surface flashover device is the key component of TVS, with its trigger characteristics depending mostly on field emission caused by the distortion of the electric field of MVD. The degree of distortion is proportional to the relative dielectric constant of the trigger dielectric material [14,15] .…”
Section: Principle Of the Surface Flashover Triggermentioning
confidence: 99%
See 1 more Smart Citation
“…From the theory of surface flashover trigger, it is shown that the surface flashover device is the key component of TVS, with its trigger characteristics depending mostly on field emission caused by the distortion of the electric field of MVD. The degree of distortion is proportional to the relative dielectric constant of the trigger dielectric material [14,15] .…”
Section: Principle Of the Surface Flashover Triggermentioning
confidence: 99%
“…In order to solve the problems of poor triggering characteristics and consumption of coating material in the high arc current, different dielectric materials are tested. The experimental results show that the dielectric material with high relative dielectric constant (ε r =2500) exhibits a high charge releasing ability and is suitable for surface flashover triggering devices [14,15] . At the same time, a special structure is designed to restrain high arc current pollution and improve the lifetime of TVS.…”
Section: Structure Of the Surface Flashover Tvsmentioning
confidence: 99%
“…Gortler [8] had studied the erosion characteristics of different ceramics, the experimental results showed that CaTiO 3 material exhibits lower erosion rate which can prolong the lifetime of the PSS. Yao et al [9] designed a ZnO semiconductor surface flashover trigger device and the experimental results showed that the ZnO flashover trigger device has excellent electron emission capability. In this paper, the experimental setups of the trigger system are built, the test method for measuring the initial plasma is presented, and the characteristics of the flashover trigger device made from ZnO dielectric material are investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is required that the crowbar discharging switch should meet special requirements, such as high hold-off voltage, short discharging delay time and delay jitter, wide operating voltage scope and high charge transferring energy. The pseudospark switch possesses the above advantages, but its low hold-off voltage limits its application to high voltage and high current circumstances, and the current peak of 10/350 µs produced by the pseudospark crowbar pulse current circuit reaches a current of only 25 kA or so [2,3] . TVS(triggered vacuum switch) integrates strong vacuum insulation characteristics into fast spark switch controlling features.…”
Section: Introductionmentioning
confidence: 99%